Management of antero posterior discrepancy using expansion appliances- A case series - Harsha G V, Durga; J, Ananth; Krishna B, Vijay; CV, Padmapriya; M, Mounica; M, Anoosha (International Journal of Dental Research, 2018)
Antero-posterior deficiencies are one of the major concerns in adolescents especially when presented with class III malocclusion and anterior cross bite. These discrepancies are generally corrected by protraction of maxilla and expansion during growth period. A 16 year old boy and 12 year old girl presented with midface deficiency with anterior cross bite and Class III malocclusion. Antero-posterior expansion was planned with Hyrax and Jack screw appliances respectively. Anterior cross bite and Class III malocclusion was corrected. Majority of these antero posterior discrepancies can be corrected with antero-posterior expansion, hence are of prime importance.Â